UiTM Green Centre collaboration with Syarikat 5 Deria Sdn. Bhd. - UiTM, UGC (UiTM Green Centre, 2025)
UiTM Green Centre had a meeting with Syarikat 5 Deria Sdn. Bhd. Another university sustainability initiative is expected to be realized through this collaboration.